The effect of buffering dairy cow diets with limestone, Acid Buf or sodium bicarbonate on production response and rumen metabolism - Mubiayi Beya, Michel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2007.